(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The right to privacy stands perceived in Indian Constitution. Article 21 accordingly secures the right to privacy as a fundamental element of the right to life and personal liberty. Right to privacy picks up significance in present situation where biometric or Adhaar ID expels duplicacy or phony IDs and in this way, is a powerful instrument to profit individuals living on edges through government welfare related plans. The present paper investigates authenticity and degree for right to privacy in changed mechanical situation, when biometrics and identity data is being put away for multipurpose utilizations including inquiry and reconnaissance.